L’identification en justice à l’époque abbasside - Mathieu Tillier (Revue des Mondes Musulmans et de la Méditerranée)
This article investigates through biographical and legal Iraqi sources how the main protagonists of the judiciary under the Abbasids in the 2nd-4th/8th-10th centuries were identified, both in proceedings and in communication between judges. The judge, the parties, the matters at issue and the witnesses had all to be identified in order to try a lawsuit; however, the legal issues involved in their identification varied according to each of these categories. While jurists agreed on physical characteristics, artefacts and names as the main elements in the process of identification, it appears that nominal identification of individuals was largely ensured by common knowledge, a concept which was theorized by Ḥanafī jurists as early as the 3rd/9th century.